STUDI GEOLOGI BAWAH PERMUKAAN RENCANA PEMBUATAN JEMBATAN LINTAS SELAT P. LAUT KABUPATEN KOTABARU KALIMANTAN SELATAN - Syaefudin, Syaefudin (Badan Pengkajian dan Penerapan Teknologi, 2006)
Subsurface geological investigation has been carried out in Pulau Laut Strai, Kotabaru Distric South Kalimantan by using seismic reflection and gravity corer methods. The aim of this suvei are identified subsurface geological features ie : litology, struktur geology and sea floor litology. The bathymetric map shows that the Suwangi Island and surrounding area have shallow water and simple geological structures. Sea floor sediment covered by sand (40%), silt (35%), gravels (15%) and silt (10%). The acoustic basement in Tanjung Ajun (first location) area shows in between 4 to 18 meters depth, while in the west and east of Suwangi Island (second location) in between 2 to 20 meters depth.